PERBANDINGAN KINERJA HASIL PENAJAMAN CITRA DENGAN PIXEL PROCESSING DAN ADOBE PHOTOSHOP 7.0 - Zuhdi, Ahmad; Erman, Alfiandi (TEKNOINFO, 2007)
Digital Image Processing represents the use of computer resources to perform correct transformation in order to produce image appearance that matching with user desire. Existing transformations have to be paid attention to, because the difference kind of transformation will influence the end result and effect that applied.This paper study to enlighten the digital image processing problem and application of a technique of Image Enhancement with Pixel Point Processing method and Pixel Group Processing method in order to produce a new image appearance that is immeasurable yielded effect. The implementation of the method realized in development of The Digital Image Processing Work Bench. The observation of this Work Bench showed performance at the process of digital image processing that have been realized, at a set of collection of data in image binding form. Evaluation of the tool performance had been conducted with a digital image processing program Adobe Photoshop 7.0, The Result of the comparison shows important improvement needs to be done for this Digital Image Processing Work Bench.